New C3H Kit N824K/WT cancer mouse model develops late-onset malignant mammary tumors with high penetrance - Klein-Rodewald, Tanja; Micklich, Kateryna; Sanz-Moreno, Adrián; Tost, Monica; Calzada-Wack, Julia; Adler, Thure; Klaften, Matthias; Sabrautzki, Sibylle; Aigner, Bernhard; Kraiger, Markus; Gailus-Durner, Valerie; Fuchs, Helmut; et al. (Scientific reports, 2022)
Gastro-intestinal stromal tumors and acute myeloid leukemia induced by activating stem cell factor receptor tyrosine kinase (KIT) mutations are highly malignant. Less clear is the role of KIT mutations in the context of breast cancer. Treatment success of KIT-induced cancers is still unsatisfactory because of primary or secondary resistance to therapy. Mouse models offer essential platforms for studies on molecular disease mechanisms in basic cancer research. In the course of the Munich N-ethyl-N-nitrosourea (ENU) mutagenesis program a mouse line with inherited polycythemia was established. It carries a base-pair exchange in the Kit gene leading to an amino acid exchange at position 824 in the activation loop of KIT. This KIT variant corresponds to the N822K mutation found in human cancers, which is associated with imatinib-resistance. C3H Kit mice develop hyperplasia of interstitial cells of Cajal and retention of ingesta in the cecum. In contrast to previous Kit-mutant models, we observe a benign course of gastrointestinal pathology associated with prolonged survival. Female mutants develop mammary carcinomas at late onset and subsequent lung metastasis. The disease model complements existing oncology research platforms. It allows for addressing the role of KIT mutations in breast cancer and identifying genetic and environmental modifiers of disease progression.